Pendidikan Multikultural dalam Usaha Meningkatkan Kesadaran HAM di Sekolah - Putri, Shanas Septina; Tiodora, Lucia; Sukmawati, Anis (AHKAM, 2023)
Multicultural education plays an important role in raising issues of mutual freedom (HAM) in schools. Through this method, students and school staff are welcome to appreciate and understand societal, racial, religious, and social diversity. Multicultural education helps combat the divisions, generalizations, and foul play that may arise in an instructive climate. Students can cultivate empathy and gain a deeper understanding of other people's points of view by studying other people's cultures and experiences. This contributes to the development of an inclusive school environment where every individual is treated with dignity and respect. Students' perceptions, attitudes, and actions regarding human rights can also be changed through multicultural education. The understanding that everyone has the same rights to be respected, recognized, and treated fairly is taught to students. They also learn about the importance of opportunities for articulation, the right to training, and other basic freedoms. The school creates an atmosphere that encourages equality, fairness, and respect for differences by implementing multicultural education. This not only makes people more aware of human rights but also helps shape a generation of students who are more tolerant, open, and ready to face an increasingly diverse world.